2006
DOI: 10.1097/01.mlg.0000195378.08969.fd
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis of Snoring Sounds by a Multidimensional Voice Program

Abstract: MDVP can be used for snoring sound analysis as a noninvasive examination of sleep-related breathing disorders for differential diagnosis. However, a suitable option that is rapid and has an easy-to-use interface would be more advantageous for analyzing snoring sounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…In general, the diVerences base mostly on the dominant frequency spectra of the snoring sounds. Palatal snoring is reported to consist of low frequency spectra (80-300 Hz), whereas tongue based snoring reveals predominately higher frequency spectra (1,000-4,000 Hz) [1,3,8,10,34]. Despite these eVorts, a precise acoustical discrimination between diVerent snoring sounds is still not possible in somnological standard diagnostic procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the diVerences base mostly on the dominant frequency spectra of the snoring sounds. Palatal snoring is reported to consist of low frequency spectra (80-300 Hz), whereas tongue based snoring reveals predominately higher frequency spectra (1,000-4,000 Hz) [1,3,8,10,34]. Despite these eVorts, a precise acoustical discrimination between diVerent snoring sounds is still not possible in somnological standard diagnostic procedure.…”
Section: Discussionmentioning
confidence: 97%
“…These individual changes in psychoacoustic parameters enable the creation of "acoustic Wngerprints" of snoring sounds to identify speciWc types of snoring and to evaluate the degree of annoyance. The frequency analysis by fast Fourier transformation (FFT) has been described as a method to investigate snoring sounds in the recent two decades [1,6,8,10,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Although MDVP has previously been used to look at soft phonation indices in snorers and OSA patients [8], our study used MDVP to try and address site -specific differences. As most our patients exhibited multilevel obstruction, we failed to highlight any obvious site-specific differences in the acoustic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This is a specific computer program which is the most widely used software for voice examination. A prospective study by Hara et al [8] concluded that MDVP can indeed be used for snoring sound analysis.…”
Section: Introductionmentioning
confidence: 98%
“…The analogy between snoring and voice stems from their common origin in the vocal tract 20 . However, voice recognition techniques have not been widely adopted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%